Model Pengembangan Kawasan Renah Kayu Embun Kota Sungai Penuh sebagai Destinasi Wisata - Silvia Rahayu (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
This study aims to determine internal and external factors, and analyze Coffee Agrotourism in Renah Kayu Embun Village. development strategies. The analysis method used in this research is descriptive analysis and SWOT analysis. The results of the internal analysis of Renah Kayu Embun Village Agrotourism have strengths including attractive conditions, low entry fees, frequent community activities, extensive agro-tourism and adequate facilities. And the weaknesses are access to tourist sites, promotions that have not been intensive, the management that has not been maximized and there is no diversification of processed products. The results of the analysis of the external environment of Renah Kayu Embun Village Agrotourism obtained opportunities, namely cooperation with other parties, in accordance with government policies issued, in accordance with human needs for holidays, there is support from the local community and opportunities for investors to develop natural resources. The threats that exist Renah Kayu Embun Village Agrotourism are the same competitors, the interest of visitors to come back, the number of visitors decreasing during the covid-19 pandemic, the development of other agro-tourism that has characteristics and pest disturbance factors that tend to be difficult to control. Various alternative strategies for Renah Kayu Embun Village Agrotourism, namely the S-O strategy. Developing Agrotourism by adding various photo and tourist spots and continuing to increase promotions, S-T Strategy such as showing the unique characteristics of Renah Kayu Embun Village Agrotourism and further improving and maintaining product quality and systems marketing, W-O strategies such as optimizing Agrotourism by continuing to develop and strengthen the business of Agrotourism, Strategy W- T is to offer discounts (rebates) both on products and agro-tourism entrance fees and provide a sense of comfort for visitors